A turn in the road [compact disc, unabridged] - Macomber, Debbie (Macomber, Debbie. Blossom Street novel., 2011)
Bethanne Hamlin takes a road trip with her daughter, Annie, and her former mother-in-law, Ruth. They're driving to Florida for Ruth's 50th high school reunion. A long-time widow, Ruth would like very much to reconnect with Royce, the love of her youth. Bethanne's ex-husband, Grant, would like to reconcile, so she also has a major life decision to consider. And Annie is out to prove to her onetime boyfriend that she can live a brilliant life without him. But even the best-laid plans can take an unexpected turn -- or even be completely derailed.